Ensuring Military-Political Security in USSR and FRG Dialogue (1987–1989) - A. I. Egorov (Научный диалог)
This article is dedicated to the examination of the diplomatic efforts undertaken by the USSR and the Federal Republic of Germany (FRG) to ensure military-political security during the period from 1987 to 1989. It explores the factors that contributed to changes in security policy. The analysis focuses on several under-researched aspects, including the strengthening of constructive forces within the federal government in 1987; the convergence of positions between the USSR and the FRG regarding disarmament and arms control; and the process of solidifying a positive trend in Soviet-West German political dialogue. Special attention is given to the role of the Free Democratic Party of Germany (FDP) in reorienting the governing coalition of the FRG from a policy of confrontation towards seeking compromises with the USSR in the realm of security. The evolution of Bonn’s official stance on the elimination of intermediate- and shorter-range missiles is also examined. It is demonstrated that, during 1988–1989, the course of the federal government became less dependent on the line of its key ally, the United States, thereby allowing for a consideration of the national interests of the FRG in addressing the issue of “nuclear rearmament”. The relevance of this study lies in its exploration of mechanisms through which the degradation of dialogue between the Russian Federation and Western collective countries in the sphere of security may be halted in contemporary times.